ANALISIS WACANA KOHESI DAN KOHERENSI PADA WACANA IKLAN POLITIK DALAM WACANA PEMILU 2014 - F, Yusep Ahmadi; Mahardika, Reka Yuda (P2M STKIP Siliwangi, 2016)
This research is discourse analysis with qualitative methods-deskriptif.Objek this study is the fruit of political advertising Gerindra Party and Democratic Party of Struggle (PDIP). The research problems are any marker of cohesion and coherence found in political advertising parati Gerindra and PDIP. Results of analysis menunujukkan cohesion markers found in the discourse of political advertising Gerindra party is katafora and reps while the discourse of political advertising PDIP is anaphora, substitution and conjunction. Meanwhile, coherence markers found in advertising Gerindra is perturutan relationship, parallelism relationship, and the relationship explanation or identification, whereas the coherence markers found in advertising discourse PDIP is perturutan relationships and relationship-knot background. These findings indicate that neither party political advertising discourse and discourse Gerindran PDIP political advertising is a good discourse and slick. Keywords: Cohesion, Coherence, Political Ads Gerindra and PDIP, Discourse Analysis